Chlamydia pneumoniae Induces Inflammatory Changes in the Heart and Aorta of Normocholesterolemic C57BL/6J Mice - Blessing, Erwin (American Society for Microbiology, 2000)
Chlamydia pneumoniae infection induces inflammatory changes in blood vessels in normocholesterolemic rabbits, but it is not known whether the same phenomenon occurs in other animal models. Thus, in this study, C57BL/6J mice were inoculated with C. pneumoniae. Inflammatory changes in the heart or aorta were observed in a small number of chronically infected mice. No evidence of atherosclerotic lesions was found in any of the mice. These findings suggest that chronic C. pneumoniae infection can induce inflammatory changes in the heart and aorta of C57BL/6J mice, but does not initiate definitive atherosclerosis.